A Literature Review of Existing Problems and Performance Influencing Factors of Expatriate Performance Management in Chinese Enterprises - Zha, Xinni (Transactions on Economics, Business and Management Research, 2024)
Research on issues related to expatriate employee performance management in Chinese enterprises can help enterprises manage their employees more scientifically and reasonably and improve their performance and efficiency. This paper aims to summary and analyse the current research trends and key issues in the field of performance management of expatriates in Chinese enterprises through a comprehensive literature review of the field. The paper summary the current situation and existing problems of performance management of expatriate employees in multinational corporations, and analyses the impact of performance management environment, irrationality of performance appraisal system, and cultural identity on reducing performance management. Meanwhile, this paper discusses the direct or indirect effects of expatriates' workplace learning, incentive mechanism differences, and expatriate adaptability on employee performance in previous studies. In addition, this paper summary the countermeasures and suggestions for optimizing expatriate performance management put forward by some studies, and on the basis of which it looks forward to improving the management system of Chinese expatriate employees.